2016
DOI: 10.1080/15592294.2016.1230576
|View full text |Cite
|
Sign up to set email alerts
|

A cross-talk between DNA methylation and H3 lysine 9 dimethylation at the KvDMR1 region controls the induction of Cdkn1c in muscle cells

Abstract: The cdk inhibitor p57 kip2 , encoded by the Cdkn1c gene, plays a critical role in mammalian development and in the differentiation of several tissues. Cdkn1c protein levels are carefully regulated via imprinting and other epigenetic mechanisms affecting both the promoter and distant regulatory elements, which restrict its expression to particular developmental phases or specific cell types. Inappropriate activation of these regulatory mechanisms leads to Cdkn1c silencing, causing growth disorders and cancer. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…As matter of fact, both DNMT1 [ 56 , 103 ], and DNMT3a [ 56 ] have been found associated with CDKN1C promoter. Consistently with the importance of DNA methylation not only in paternal allele imprinting but also in p57 Kip2 expression modulation in specific cellular and cell cycle phase contexts, treatment of many human tumor cell lines with demethylating agents such as 5-azacytidine and 5-aza-2′-deoxycytidine results generally in p57 Kip2 expression activation [ 102 , 104 ].…”
Section: Control Of Cdkn1c Transcriptionmentioning
confidence: 90%
See 1 more Smart Citation
“…As matter of fact, both DNMT1 [ 56 , 103 ], and DNMT3a [ 56 ] have been found associated with CDKN1C promoter. Consistently with the importance of DNA methylation not only in paternal allele imprinting but also in p57 Kip2 expression modulation in specific cellular and cell cycle phase contexts, treatment of many human tumor cell lines with demethylating agents such as 5-azacytidine and 5-aza-2′-deoxycytidine results generally in p57 Kip2 expression activation [ 102 , 104 ].…”
Section: Control Of Cdkn1c Transcriptionmentioning
confidence: 90%
“…Complete biallelic hypermethylation occurs in human tumors and tumor cell lines [ 100 , 101 ], as well as in some undifferentiated tissues and cell types such as skeletal myoblasts. In this cell model, the activation of the transcription factor MyoD drives DNA demethylation on the maternal allele, therefore allowing the Myo- d -dependent expression of p57 Kip2 [ 102 ].…”
Section: Control Of Cdkn1c Transcriptionmentioning
confidence: 99%
“…It is reported that the Kcnq1 gene, expressed in various tissues of the body, has an important physiological role in regulating water and salt metabolism [12]. Kcnq1 and Cdkn1c are 2 adjacent imprinted genes that are expressed from the maternal [13]. Interestingly, there is a relationship between abnormal imprinting genes and growth and development of various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Among the HKMT family, G9a and G9a-like protein (GLP) are two HKMTs that catalyze H3K9me1 and H3K9me2, and with Suv39H1, Suv39H2, and SETDB1, complete the SET-containing SUV39 protein family responsible for H3K9 methylation, an epigenetic modification found to be dependent on DNA methylation in human cancer cells [74,75,76]. G9a and GLP apparently form a functional heteromeric complex with in vivo H3K9 methyltransferase activity [76,77,78,79].…”
Section: Inhibition Of Histone Methylationmentioning
confidence: 99%
“…Indeed, DNA methylation is lost in G9a or GLP -mutated cells. G9a and GLP can recruit DNMT3a and DNMT3b directly or indirectly through the chromodomain protein M-phase phosphoprotein 8 (MPP8), leading to de novo DNA methylation [75,85,86,87,88]. …”
Section: Inhibition Of Histone Methylationmentioning
confidence: 99%